Effect of Turmeric Concentrations on the Rate of Growth of Oral Bacteria-An In-Vitro Study - Yun Xuan Yang; Vicky Wu; Hadi Malak; Aliya Peer Ahamed; Aaron Lo; Yannis Abraham; Catherine Miller (MDPI AG, 2021)
Background and Aim: The aim of this study was to evaluate the effect of varying concentrations of a turmeric solution on the growth rates of oral bacteria sampled from dental students. Methods: Bacterial cultures were grown overnight in aerobic conditions from plaque samples obtained from five test subjects. With the exception of the control, samples were exposed to different treatments; including chlorhexidine gluconate 2 mg/mL, prepared turmeric solution (TS) mouthwash: TS 0.25 mL (7.375 mg/mL), TS 0.5 mL (14.75 mg/mL), and TS 1 mL (29.50 mg/mL). Growth rate of the bacterial cultures were assessed by monitoring changes in optical density readings at 600 nm at hourly intervals for a six-hour period. The data were plotted and the exponential trend was used to calculate individual rates of growth. Data was analyzed using a one-way ANOVA with the significance confirmed using the Tukey-HSD test. Results: Growth observed in the bacteria exposed to the turmeric solution, was significantly greater (p < 0.05) when compared with the bacteria exposed to the medium alone. There was a significant difference found between the bacterial growth rate of the 1 mL turmeric solution against the growth rate of the bacteria in the 0.25 and 0.5 mL turmeric solutions. Conclusion: Comparison of growth rates of oral bacteria suggested that turmeric solutions of concentrations between 7.357 and 29.5 mg/mL (0.25-1 mL) were unlikely to exhibit bacteriostatic or bactericidal properties, and, conversely, increased bacterial growth. Considering this result, it is unlikely that turmeric mouthwash made from store-bought turmeric would have any antibacterial effects against oral bacteria, and may even promote bacterial growth.